Social influence and individual self: engaging business students in sustainability transformation - Ali Kara; John E. Spillan; Guido Grunwald (International Review on Public and Nonprofit Marketing, 2025)
The objective of this study is to uncover distinct segments of business students in international study using their intentions to actively engage in the sustainability transformations of their higher education institutions (HEIs). By utilizing the SHIFT framework and analyzing the individual self and social influence dimensions of students, we seek to explain their tendency to engage in HEIs' sustainability efforts. A quantitative study design was employed, and data from 239 business students were collected in two countries through an online survey. Cluster analysis and ANOVA were used to develop and interpret the segments. Findings reveal two distinct categories among business students—Actives and Passives—based on their behavioral intentions. The segments differ in terms of sustainability interests, transformation expectations, and collectivism orientation. Each segment can be further divided into subsegments according to their collectivism orientations. Using the SHIFT framework, more refined segment-based strategies are developed to enhance students' engagement in sustainability at HEIs. This study addresses the gap in understanding the individual value priorities of business students and their engagement in sustainability across various cultural and environmental contexts. It also contributes to a better understanding of students' expectations concerning the sustainability transformations of HEIs. By employing a theoretically sound framework, SHIFT, this study provides practical implications and measures for effectively engaging students in the sustainability transformation process within HEIs.
Keywords: 380; Sustainability transformation; Higher education; Segmentation; Collectivism; SHIFT framework